Bioengineered glaucomatous 3D human trabecular meshwork as an in vitro disease model. Issue 6 (30th December 2015) - Torrejon, Karen Y.; Papke, Ellen L.; Halman, Justin R.; Stolwijk, Judith; Dautriche, Cula N.; Bergkvist, Magnus; Danias, John; Sharfstein, Susan T.; Xie, Yubing
ABSTRACT: Intraocular pressure (IOP) is mostly regulated by aqueous humor outflow through the human trabecular meshwork (HTM) and represents the only modifiable risk factor of glaucoma. The lack of IOP‐modulating therapeutics that targets HTM underscores the need of engineering HTM for understanding the outflow physiology and glaucoma pathology in vitro. Using a 3D HTM model that allows for regulation of outflow in response to a pharmacologic steroid, a fibrotic state has been induced resembling that of glaucomatous HTM. This disease model exhibits HTM marker expression, ECM overproduction, impaired HTM cell phagocytic activity and outflow resistance, which represent characteristics found in steroid‐induced glaucoma. In particular, steroid‐induced ECM alterations in the glaucomatous model can be modified by a ROCK inhibitor. Altogether, this work presents a novel in vitro disease model that allows for physiological and pathological studies pertaining to regulating outflow, leading to improved understanding of steroid‐induced glaucoma and accelerated discovery of new therapeutic targets. Biotechnol. Bioeng. 2016;113: 1357–1368. © 2015 Wiley Periodicals, Inc. Abstract : A perfusable glaucomatous 3D human trabecular meshwork (HTM) model has been created and characterized. Microfabricated, well‐defined, porous scaffolds are used to culture primary HTM cells in 3D, followed by glaucomatous induction using a steroid. Steroid‐induced, glaucomatous HTM alterations can be alleviated by a ROCK inhibitor. This novel model provides a new avenue for pathophysiological studies, drug testing and target discovery.